Proteomic analysis revealed the pharmacological mechanism of Xueshuantong injection in preventing early acute myocardial infarction injury - Wang, Aoao; Li, Ying; Wang, Ziyan; Xin, Gaojie; You, Yue; Sun, Mingqian; Miao, Lan; Li, Lei; Pan, Yinghong; Liu, Jianxun (Frontiers in Pharmacology, 2022)
Abstract Background: Acute myocardial infarction (AMI) is a common and life-threatening cardiovascular disease. However, there is a lack of pathology and drug studies on AMI within 20 min. Xueshuantong injection (XST) is mainly composed of panax notoginseng saponins, which can dilate blood vessels and improve blood circulation, and is clinically used in the treatment of cardiovascular and cerebrovascular diseases. Purpose: To investigate the protective mechanism of XST against AMI within 20 min in rats by proteomic methods and molecular docking. Method: Male Sprague-Dawley rat acute myocardial infarction model was established by LAD ligation, and XST (38 mg/kg) was injected into the caudal vein 15 min before surgery. Cardiac function evaluation, morphological observation, lable-free quantitative proteomics, western blotting analysis, molecular docking and affinity measurement were applied in this study. Results: Twenty minutes after AMI, the model group showed significant cardiac function impairment. XST can significantly improve cardiac function and prevent pathological injury of myocardial tissue. A total of 117 vital differentially expressed proteins identified by Proteomic analysis, including 80 differentially expressed proteins (DEPs) in Sham group compared with Model rats (Sham:Model), and 43 DEPs in Model rats compared with XST group (Model:XST). The treatment of XST mainly involves "Poly(A) RNA binding" and "Cadherin binding involved in cell-cell adhesion". The differentially expressed levels of the pathways related proteins Echdc2, Gcdh, Dlst, Nampt, as well as 14-3-3 family protein Ywhaz and Ywhab could be quantitatively confirmed by WB. Molecular docking analysis and SPR analysis revealed that Ywhaz has a general stable binding with five XST components. Conclusion: Xueshuantong injection (XST) could protect rat myocardial function injury against AMI in 20 min. Echdc2, Ywhaz, Gcdh, Ywhab,Nampt, and Dlst play an essential role in this protection effect. Especially, Ywhaz might be the core target of XST when treating AMI in the early stage. This study promoted the understanding of the protective mechanism of XST on 20 min injury of AMI, and contributed to the identification of possible targets of XST.